ChemInform Abstract: Synthesis of 2‐Alkylidene‐3, 1‐benzoxathiin‐4‐ones by the Pummerer Type Reaction. Issue 45 (November 2015) - Yamanaka, Masaki; Shimada, Shigeru; Ando, Wataru; Konakahara, Takeo; Sakai, Norio; Shimizu, Masao
Abstract Review: 3 refs.